Later-Life Living Arrangements of Americans With and Without Children: A Life Table Approach. (14th July 2021) - Raymo, James M; Xu, Xiao; Kim, BoRin; Liang, Jersey; Ofstedal, Mary Beth
Abstract: Objectives: This study describes living arrangement-specific life expectancy for older Americans with and without children, by sex and race/ethnicity. Method: We use life tables from the Human Mortality Database and data from the Health and Retirement Study over a 17-year period (2000–2016) to calculate living arrangement-specific life expectancy at age 65 using Sullivan's method. Results describe the lives of older Americans aged 65 and older with and without children in terms of the number of expected years of life in different living arrangements. Results: With the exception of Hispanic men, older Americans without children spend over half of their remaining life living alone. Among the childless, it is White women and Black men who spend the largest percent of remaining life living alone (65% and 57%, respectively). Relative to parents, childless older Americans have an overall life expectancy at age 65 that is 1 year lower and spend 5–6 years more living alone and fewer years living with a spouse (8 years less for men and 5 years less for women). Childless older Americans spend more time in nursing homes, but average expected duration in this living arrangement is short and differences between those with and without children are small. Discussion: This descriptive analysis demonstrates the fundamental ways in which children shape the lives of older Americans by showing that later-life living arrangements of childless Americans differ markedly from their counterparts with children. These results provide a valuable empirical foundation for broader efforts to understand relationships between childlessness, living arrangements, and well-being at older ages.